A CONSTRUÇÃO DE UM 'BAD ROMANCE': UM ESTUDO SEMIÓTICO DA INTERTEXTUALIDADE NA DRAMATIZAÇÃO DE PROBLEMAS SOCIAIS EM TRÊS VIDEOCLIPES DE LADY GAGA​ - Euclides Vieira de Sousa Filho (2023)
Singer Lady Gaga (b.1986) can be considered a spokesperson for her generation, as she proposes to discuss problems, especially those of youth, experienced by her fans, which she calls Little monsters. Issues such as gender fluidity, respect for the LGBTQIAP+ community and mental illness are some of the ones that are present in the singer's songs. Considering Lady Gaga's videography, her aspects of autobiographical and engaged art stand out for us, in parallel with the mixture of signs from different languages, among which are references to works by other artists. We understand this as generating an intertextuality associated with the dramatization of social problems. And it is this intertextuality that we take as an object of study in this dissertation, analyzed in three video clips of this singer: Born This Way (2011); Applause (2013) and 911 (2020). The theoretical-methodological framework adopted for the research correlates the concepts of dialogism, polyphony and intertextuality by Mikhail Mikhailovich Bakhtin (1895-1975), with semiotic concepts by Charles Sanders Peirce (1839-1914), pertinent to meaning, objectification and interpretation. The analysis of the three selected video clips, in addition to recognizing that the mixture of signs is made possible by the use of digital information and communication technologies, allows us to visualize how these video clips are referencing and promoting dialogue with other works, already known by the interpreter of audiovisual culture. Considering that this strategy leads to the construction of a dramatic, autobiographical discourse thematically related to social problems experienced by its audience, we proposed classifying video clips as engaged art. We conclude the research by highlighting, through these works, signs organized in an intertextual discourse that speak of problems experienced by the singer herself and, also, that are common to part of her generation; they are personal dramas, some involving risks to the health of those who experience them. They are the subject of songs and music videos, which is why we interpret such works as containing the narrative of a bad novel (Bad romance). The contributions of this dissertation, in addition to addressing social problems still present today, focus on the relationship between language studies, the music video, engaged art and contemporary pop music.